2011
DOI: 10.1371/journal.ppat.1002203
|View full text |Cite
|
Sign up to set email alerts
|

Complex Recombination Patterns Arising during Geminivirus Coinfections Preserve and Demarcate Biologically Important Intra-Genome Interaction Networks

Abstract: Genetic recombination is an important process during the evolution of many virus species and occurs particularly frequently amongst begomoviruses in the single stranded DNA virus family, Geminiviridae. As in many other recombining viruses it is apparent that non-random recombination breakpoint distributions observable within begomovirus genomes sampled from nature are the product of variations both in basal recombination rates across genomes and in the over-all viability of different recombinant genomes. Where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
96
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(106 citation statements)
references
References 65 publications
9
96
0
1
Order By: Relevance
“…In addition, recombination breakpoint distributions found in both field-isolated geminiviruses and geminiviruses arising during recombination experiments display well-defined hot and cold spots (26,45,46,(48)(49)(50) that can strongly influence the efficiency of adaptive evolution via recombination (27). Here, however, we observed little evidence of recombination occurring at known recombination hot spots in the MSV genome and, in fact, found a number of breakpoints falling within known recombination cold spots (Fig.…”
Section: Agrobacterium Tumefaciens-mediated Delivery Into Suitable Plmentioning
confidence: 57%
See 1 more Smart Citation
“…In addition, recombination breakpoint distributions found in both field-isolated geminiviruses and geminiviruses arising during recombination experiments display well-defined hot and cold spots (26,45,46,(48)(49)(50) that can strongly influence the efficiency of adaptive evolution via recombination (27). Here, however, we observed little evidence of recombination occurring at known recombination hot spots in the MSV genome and, in fact, found a number of breakpoints falling within known recombination cold spots (Fig.…”
Section: Agrobacterium Tumefaciens-mediated Delivery Into Suitable Plmentioning
confidence: 57%
“…Previous studies involving both natural and laboratory-derived geminiviruses that are related to MSV indicated that recombination breakpoints tend to cluster within noncoding regions of the genome. This pattern is probably due to both the mechanistic predisposition for recombination breakpoints in geminiviruses to occur at replication origins and selective forces disfavoring the survival of recombinants encoding chimeric proteins (18,(45)(46)(47)(48)(49). To the right of the phylogenetic tree is a linearized genome schematic showing the pattern of recombination and the number of breakpoints in each group of recombinant MSVs, where genomic regions in blue are derived from sMSV1 and regions in brown are derived from sMSV2.…”
Section: Agrobacterium Tumefaciens-mediated Delivery Into Suitable Plmentioning
confidence: 99%
“…These portions were exchanged as blocks that preserve them as originating from the same genetic background. This could increase the frequency in which viable recombinants for the Rep sequence are maintained by preserving the interaction between the catalytic domains (in the Rep N-terminal portion) and their cognate iterative elements located in the 59 portion of the common region (Martin et al, 2011). Although a reduced number of breakpoints occur within the CP-encoding sequence, most of them are located in the central portion of the gene (Lefeuvre et al, 2007b).…”
Section: Recombination and The Genetic Structure Of Begomovirus Populmentioning
confidence: 99%
“…Geminiviruses typically carry genes that encode 5 to 7 proteins that interact with a wide array of host proteins to reprogram plant cell cycle and transcriptional controls, interfere with cell signaling and protein turnover, and suppress defense pathways. Geminiviruses also display high mutation and recombination rates that allow them to adapt rapidly to new environments and new hosts (6,7). This rapid adaptation in combination with a long evolutionary history with their plant hosts has provided many opportunities for geminiviruses to modulate interactions with their hosts and enhance their success as pathogens (8).…”
mentioning
confidence: 99%